Prólogo para o Alto Rendimento - da conceção à operacionalização de uma época desportiva com nadadores infantis do Leixões Sport Club - Edgar Francisco Teixeira Ribeiro (2019)
Planning a sporting season is a meticulous process that requires articulating several factors on behalf of the trainer. Being successful in sports depends on the training, which in turn, is based on physiological, biomechanical and psychological factors and their harmonious coexistence. This process is the result of combining concepts such as sports, physical training, coaching in general and coaching young people, being a swimmer, swimming, sports performance, strength training, flexibility training, water training, psychology, nutrition, injury prevention, training evaluating and controlling, analysing results, evolution and interpersonal relations.It is about reflecting on the concept (theory) and the methodology (practice) that substantiate the decisions made throughout the sporting season. To organise this internship report, meant taking into consideration the design, planning and operationalisation the children's section sports season of 2017/2018, of the swimming section of Leixões Sport Club. This assignment was elaborated with 20 federated swimmers, by the Portuguese Swimming Federation, equally distributed by both sexes, with 11.69 ± 0.87 (years) of age, 43.99 ± 8.81 (kg) in body weight, 155.44 ± 10.83 (cm) in height, 157.88 ± 12.31 (cm) in scale/wingspan and a body mass index of 18.23 ± 2.90 (weight / height2). Through the championships' access times, 11 swimmers were present at the pinnacle of the sporting season: the National Championships. We hope that by sharing all the information present in this assignment, whether it's the ideas, the experiences or the results, it is possible to develop the concept of swimming, in both a theoretical and practical matter, to other coaches with similar goals.